Daughter Zion : her portrait, her response - Boda, Mark J.; Dempsey, Carol J.; Flesher, LeAnn Snow. (Atlanta : Society of Biblical Literature, 2012)
This volume showcases recent exploration of the portrait of Daughter Zion as "she" appears in biblical Hebrew poetry. Using Carleen Mandolfo's Daughter Zion Talks Back to the Prophets as a point of departure, the contributors of this volume explore the image of Daughter Zion in its many dimensions in various texts in the Hebrew Bible. Approaches used range from poetic, rhetorical, and linguistic to sociological and ideological. --From publisher's description.
Cognitive linguistics and the "idolatry-is-adultery" metaphor of Jeremiah 2-3 / Barbara Green -- Speaking of speaking : the form of Zion's suffering in Lamentations / Jill Middlemas -- Isaiah 40-55 : a Judahite reading drama / Lena-Sofia Tiemeyer -- The fecundity of fair Zion : beauty and fruitfulness as spiritual fulfillment / Stephen L. Cook -- Daughter Zion : metaphor and dialogue in the book of Lamentations / Mary L. Conway -- Yhwh as jealous husband : abusive authoritarian or passionate protector? : a reexamination of a prophetic image / Brittany Kim -- Zion's plea that God see her as she sees herself : unanswered prayer in Lamentations 1-2 / John F. Hobbins --The Daughter of Zion goes fishing in heaven / Michael H. Floyd -- Ezekiel 16 : shared memory of Yhwh's relationship with Jerusalem : a story of fraught expectations / Mignon R. Jacobs -- Zion's body as a site of God's motherhood in Isaiah 66:7-14 / Christl M. Maier -- Demonized children and traumatized, battered wives : Daughter Zion as biblical metaphor of domestic and sexual violence / Cheryl A. Kirk-Duggan -- Mission not impossible : justifying Zion's destruction and exonerating the common survivors / Kim Lan Nguyen -- Daughter Zion : codependent no more / LeAnn Snow Flesher -- The daughter's joy / Mark J. Boda -- "Whose God is this anyway?" : a response to Carleen Mandolfo / Carol J. Dempsey -- Daughter Zion talks back to her interlocutors / Carleen Mandolfo.
Contributions partly in response to title: Daughter Zion talks back to the prophets: a dialogic theology of the book of Lamentations / Carleen R. Mandolfo (Atlanta : Society of Biblical Literature, c2007) and feminine images within the Hebrew Bible, especially as related to the relationship between Zion and God.
Includes bibliographical references (pages 369-400) and indexes.
Keywords: Mandolfo, Carleen; Bible. -- Criticism, interpretation, etc; Personification in the Bible; Jerusalem -- In the Bible